Online and campus college students like using an open educational resource instead of a traditional textbook - Lindshield, Brian L.; Adhikari, Koushik (My University, 2013)
There has been little research on student use and perception of open educational resources that are used to replace traditional textbooks/e-textbooks. The creation of the Kansas State University Human Nutrition Flexbook, and online and campus students' perceptions and usage of the flexbook, have been reported previously based survey results from a single semester. Results from multiple online and campus semesters are reported in this paper. Both online and campus students rated the flexbook favorably, but online students used the flexbook more frequently, liked the idea of the flexbook more, and rated it as being of higher quality. Online students also liked and used the animations, videos, and links more and liked the appearance and flexibility of the flexbook more than campus students. The majority of students used an electronic flexbook format and more than one flexbook format. The Portable Document Format version, followed by the Google Docs version, were the most commonly used primary formats. Overall, responses across multiple semesters confirm the authors' original findings that students like using the flexbook instead of a traditional textbook.
Keywords: Digital textbook; E-textbook; E-book; Flexbook; Open access; Open educational resources; Student perceptions